Informação & Informação:v. 19, n. 3 (2014) - Bandeira, Pablo Matias (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2015)
Link de acesso ao Número: http://www.uel.br/revistas/uel/index.php/informacao/issue/view/979